2017
DOI: 10.2174/1874210601711010079
|View full text |Cite
|
Sign up to set email alerts
|

Laser Assisted Non-surgical Periodontal Therapy: A Double Blind, Randomized Clinical Trial

Abstract: The objective of this study was to examine potential benefits of using laser therapy for secular decontamination in conjunction with scaling and root planing in the treatment of chronic periodontitis. The study was performed on 173 teeth in 14 patients in a split-mouth design, one side received scaling and root planing followed by laser therapy using a carbon dioxide (CO2) laser with an ablative handpiece (test group); the contralateral side received scaling and root planing without laser (control group). Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…By screening titles and abstracts, 71 articles were reserved for full‐text reading and the rest was eliminated. After a detailed assessment of full text, 16 qualified articles remained for our meta‐analysis (Aykol et al., 2011 ; Dereci et al., 2016 ; Eltas & Orbak, 2012 ; Euzebio Alves et al., 2013 ; Everett et al., 2017 ; Gundogar et al., 2016 ; Magaz et al., 2016 ; Makhlouf et al., 2012 ; Rotundo et al., 2010 ; Saglam et al., 2014 ; Sanz‐Sanchez et al., 2015 ; Sezen et al., 2020 ; Ustun et al., 2014 , 2018 ; Zengin Celik et al., 2019 ; Zhou et al., 2019 ). The flow diagram of the study selection is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…By screening titles and abstracts, 71 articles were reserved for full‐text reading and the rest was eliminated. After a detailed assessment of full text, 16 qualified articles remained for our meta‐analysis (Aykol et al., 2011 ; Dereci et al., 2016 ; Eltas & Orbak, 2012 ; Euzebio Alves et al., 2013 ; Everett et al., 2017 ; Gundogar et al., 2016 ; Magaz et al., 2016 ; Makhlouf et al., 2012 ; Rotundo et al., 2010 ; Saglam et al., 2014 ; Sanz‐Sanchez et al., 2015 ; Sezen et al., 2020 ; Ustun et al., 2014 , 2018 ; Zengin Celik et al., 2019 ; Zhou et al., 2019 ). The flow diagram of the study selection is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Laser therapy effective in periodontal treatment and there is ongoing debate regarding the efficacy of lasers in periodontal disease. [50][51][52][53] The American Dental Association's (ADA) and American Academy of Periodontology's (AAP) recommendations regarding their use in treating periodontal disease. 54 Since the role of periodontal pathogens in the etiology of peri-implantitis is indisputable, this indicates that anti-infection therapy for periimplantitis should be consistent with the treatment strategy for periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in BOP was 42% at the test site and 37% at the control site. In another study [ 54 ], for all sites having PD of 5.0 mm or higher after three months, the PD decrease was 1.73 mm (1.50 mm CAL gain) in the test site and 1.58 mm (1.21 mm CAL gain) in the control site. In contrast, the PD decrease was 2.02 mm (1.83 mm CAL gain) at the test site and 1.42 mm (1.44 mm CAL gain) at the control site for all sites with PD of 5.0 mm or above at six months.…”
Section: Reviewmentioning
confidence: 98%
“…Similarly, Everett JD and colleagues [ 54 ] conducted a split-mouth study to investigate the benefits of adding CO2 laser (1st pass: 25-50 J/cm2 at 4 watts CW and 2nd pass: 75-100 J/cm2 at 8 watts CW) treatment for sulcular decontamination to SRP in the management of chronic periodontitis. The research involved 173 teeth from 14 participants.…”
Section: Reviewmentioning
confidence: 99%